Contribution to the field of traffic assignment: A boundedly rational user equilibrium model with uncertain supply and demand. (April 2021) - Xu, Junxiang; Zhang, Jin; Guo, Jingni
Abstract: Since the existing models and algorithms cannot well deal with the traffic assignment problems under uncertain supply and demand conditions, this paper proposes a traffic assignment model based on cumulative prospect theory. Firstly, the cumulative prospect theory is extended on the basis of a large number of numerical analysis experiments and the road impedance function of road segments is improved. Then, by setting the reference point of fuzzy generalized cost and the reference point of staged dynamic risk degree of road segment, the comprehensive cumulative prospect value (CCPV) function is improved, a boundedly rational user equilibrium (BRUE) model under uncertain supply and demand conditions is constructed, and an isolation niche genetic simulated annealing algorithm (INGSAA) is designed to solve the model. Finally, taking the road network of the Sichuan-Tibet region in China as an example, the processes of boundedly rational equilibrium under the fixed and variable network structure are investigated, and the relevant parameters are analyzed. The research results verify that the BRUE model based on the extended cumulative prospect theory provides a good idea for solving the problem of traffic assignment under uncertain supply and demand conditions, which is of great theoretical significance and application value. Highlights: Comprehensive cumulative prospect value function is given with the preference of multiple reference points considered. Impedance function is designed for the traffic segments after considering cost and uncertain network supply. Isolation niche genetic simulated annealing algorithm is proposed to solve the model.